Levothyroxine Administration during Ramadan: A Prospective Randomized Controlled Trial. Issue 6 (10th November 2021) - El-Kaissi, Samer; AbdelWareth, Laila; Dajani, Ruba; Lee-St. John, Terrence J.; Santarina, Sherry Ann; Makia, Fiona; AlTakruri, Malak; Kaskas, AbedElRahman; Ahmed, Yahya
Abstract : Background and Aim: We have previously shown in a retrospective analysis that the plasma thyroid-stimulating hormone (TSH) rises significantly post-Ramadan in levothyroxine-treated hypothyroid patients, possibly as a result of lifestyle alterations and time restrictions during the nonfasting period from dusk until dawn. The aim of this study is to determine the best time to instruct patients to take levothyroxine during Ramadan so as to minimize changes in thyroid function tests during this period. Methods: In a randomized prospective design, hypothyroid patients taking levothyroxine were randomized to receive instructions to take levothyroxine at one of the following 3 times during Ramadan: (group 1) at dusk 30-min before Iftar meal, (group 2) 3 or more hours after Iftar meal, or (group 3) at dawn 30-min before Suhur meal. Thyroid function tests were performed within 3 months before Ramadan and within 6 weeks post-Ramadan. Data from patients with at least 1 blood test before or after Ramadan were analyzed using mixed-effects regression models. Results: Plasma TSH levels were available at one or more time points for 148 patients, group 1 ( n = 50), group 2 ( n = 46), and group 3 ( n = 52). A statistically significant within-patient increase in plasma TSH was seen in patients at the 25th percentile pre-Ramadan in groups 2 and 3 ( p values <0.001), but not in group 1. A statistically significant within-patient decrease in plasma TSH was found in patients at the 75th percentile in group 1 only. For patients at the 50th percentile pre-Ramadan, no statically significant within-patient changes were found, though descriptively, increases in plasma TSH were observed for groups 2 and 3, while a decrease was observed in group 1. Conclusions: Our data suggest that instructing patients to take levothyroxine at the time of breaking the fast 30 min before the Iftar meal minimizes unfavorable changes in plasma TSH post-Ramadan. In contrast, instructing patients to take levothyroxine 3 h post-Iftar or 30 min before Suhur led to a greater rise in post-Ramadan TSH.